2021
DOI: 10.1007/s11357-021-00483-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell-derived small extracellular vesicles promote neurological recovery and brain remodeling after distal middle cerebral artery occlusion in aged rats

Abstract: Small extracellular vesicles (sEVs) obtained from mesenchymal stromal cells (MSCs) promote neurological recovery after middle cerebral artery occlusion (MCAO) in young rodents. Ischemic stroke mainly affects aged humans. MSC-sEV effects on stroke recovery in aged rodents had not been assessed. In a head-to-head comparison, we exposed young (4–5 months) and aged (19–20 months) male Sprague–Dawley rats to permanent distal MCAO. At 24 h, 3 and 7 days post-stroke, vehicle or MSC-sEVs (2 × 106 or 2 × 107 MSC equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
(100 reference statements)
2
27
0
Order By: Relevance
“…In line with our findings, Cho et al have shown that CM derived from human MSCs elevates number of CD31‐positive microvessels in the penumbra following MCAO 16 . Recently, it has been reported that three times systemic injections of EVs derived from human BM‐MSCs could increase number of CD31 + /BrdU + microvessels and promote angiogenesis in the peri‐infarct cortex of ischemic rats 51 . It should be noted the newly generated capillaries may also pose major concerns including edema formation, hemorrhagic transformation, and BBB damage.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our findings, Cho et al have shown that CM derived from human MSCs elevates number of CD31‐positive microvessels in the penumbra following MCAO 16 . Recently, it has been reported that three times systemic injections of EVs derived from human BM‐MSCs could increase number of CD31 + /BrdU + microvessels and promote angiogenesis in the peri‐infarct cortex of ischemic rats 51 . It should be noted the newly generated capillaries may also pose major concerns including edema formation, hemorrhagic transformation, and BBB damage.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we also showed that rats receiving three injections of hESC‐MSC‐CM exhibit decreased mRNA level of IL‐6 as well as increased mRNA level of IL‐10 relative to ischemic rats. Similarly, intravenous injection of EVs obtained from MSCs has been shown to induce anti‐inflammation properties and reduce infiltration of immune cells in ischemic brains of aged mice on 7‐day post‐MCAO as well as microglia accumulation in the peri‐infarct cortex of young rats on 28‐day post‐MCAO 51,60 . Moreover, in several studies strong anti‐inflammatory and immunomodulatory properties of ESC‐MSC have been revealed.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Extracellular vesicles with lipid bilayer structures, such as exosomes and microvesicles (MVs), are secreted by mesenchymal stromal cells [ 25 ], neural stem cells [ 26 ], microglia [ 27 ] and other cell types. These vesicles can fuse with the cell membrane, providing a way for the vesicle contents to be transported between cells and for the vesicles to escape phagocytosis by endothelial reticular cells, thereby stabilizing them in the circulation [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%